Identification of the Babesia-responsive leucine-rich repeat domain-containing protein from the hard tick Haemaphysalis longicornis - Maeda, Hiroki; Kurisu, Koshi; Miyata, Takeshi; Kusakisako, Kodai; Galay, Remil Linggatong; Rio, Talactac Melbourne; Mochizuki, Masami; Fujisaki, Kozo; Tanaka, Tetsuya (Parasitology research (1987), 2015)
Haemaphysalis longicornis is a tick known for transmitting Babesia parasites, including Babesia gibsoni, in East Asian countries. The vector tick must have strategies to control Babesia parasites, while Babesia parasites are also considered to establish an evasive mechanism from the tick’s innate immunity. Due to this mutual tolerance, H. longicornis is considered to be a vector of Babesia parasites. Recent studies have shown the important roles of leucine-rich repeat (LRR) domain-containing proteins in innate immunity in many living organisms. Some LRR domain-containing proteins were identified in ticks; however, their functions are still unknown. In this study, a novel LRR domain-containing protein was identified from H. longicornis (HlLRR). HlLRR contains two LRR domains, and the expression levels of mRNA and proteins were upregulated during blood feeding, particularly in the salivary glands and midgut. In addition, recombinant HlLRR (rHlLRR) demonstrated growth inhibition activity against B. gibsoni in vitro without a hemolytic effect at any concentration used. Moreover, the diameters of Babesia merozoites treated with rHlLRR were significantly larger than those of the control group. These results strongly indicate the key roles of HlLRR in the tick’s innate immunity against Babesia parasites. Furthermore, HlLRR might be a potential alternative drug to treat babesiosis.